"Ramp lesions" of the posterior segment of the medial meniscus: what is repaired? An anatomical and histological study. Issue 2 (28th February 2020) - Nicolas, Quentin; Francia, Rémi Di; Le Henaff, Goulven; Quintin-Roue, Isabelle; Gunepin, François-Xavier; Dubrana, Frédéric
Background: Lesions of the posterior segment of the medial meniscus are the most common intra-articular lesions associated with anterior cruciate ligament injury. "Ramp lesions" have been defined as a tear in the peripheral attachment of the posterior horn of the medial meniscus (PHMM). These injuries are difficult to detect on preoperative MRI, whereas their prevalence with arthroscopy can be as high as 24%. The management of "Ramp lesions" isn't collegiale. There are only two publications in PUBMED concerning anatomic and histological description posterior menisco-tibial ligament ( PMTL). The objective of this histological study was to analyze the posterior segment of the medial meniscus and its meniscosynovial junction, in order to identify the PMTL. Methods: We dissected ten cadaveric knees. A posterior approach to the posteromedial capsule was used. Therefore, we were able to access the posterior segment of the medial meniscus and its meniscosynovial junction. The proximal capsule, the posterior segment of the medial meniscus, the entire meniscal capsular-tibial junction, and a fragment of the tibia were removed together. For each part, three section slices were prepared for the histological study. Results: Macroscopically, the meniscotibial attachments was pellucid, homogeneous. The meniscocapsular attachments was pellucid, homogeneous but appeared to be strengthened at both the anterior and posterior portions of the capsule. The microscopic study of meniscosynovial jonction revealed loose collagen fibers, oriented but not organized parallel, network with rare fibroblasts and and adipocytes, several capillaries were seen. No histological differences were observed, and the 2 attachments merged at a common attachment site on PHMM. Conclusion: For us, "Ramp lesion" is a tear of common attachment of menicocapsular and meniscotibial junctions of PHMM. This attachment is vascularized, an outfit is possible and biomechanical role is increasingly identified.